1993
DOI: 10.1007/bf02125443
|View full text |Cite
|
Sign up to set email alerts
|

Hormonal and molecular genetic findings in 46,XX subjects with sexual ambiguity and testicular differentiation

Abstract: Ten patients were studied who had sexual ambiguity having in common a 46.XX karyotype and testicular tissue. They were aged from one month to 23 years; some of them were followed through puberty. Eight cases were sporadic and two familial. They were divided into two groups according to finding of surgery and histology: 46, XX males with sexual ambiguity and 46 XX true hermaphrodites (TH). They were no differences in phenotypes (except uterus and ovotestis in TH). The endocrinological data were identical in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
8
0
1

Year Published

1995
1995
2020
2020

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 22 publications
2
8
0
1
Order By: Relevance
“…Alves et al [2010] suggested that negative XX testicular DSD may result due to gain-of-function mutations in one or more genes downstream to the SRY gene pathway or due to a loss of function in some genes associated with the inhibition of male development. It has been postulated that Y-negative XX testicular DSD and XX OT-DSD have a common origin [Toublanc et al, 1993;Kolon et al, 1998], which is supported by many reports of sibship among XX males and XX OT-DSD [Abbas et al, 1990;Ramos et al, 1996;Slaney et al, 1998;Maciel-Guerra et al, 2008].…”
Section: Discussionsupporting
confidence: 57%
“…Alves et al [2010] suggested that negative XX testicular DSD may result due to gain-of-function mutations in one or more genes downstream to the SRY gene pathway or due to a loss of function in some genes associated with the inhibition of male development. It has been postulated that Y-negative XX testicular DSD and XX OT-DSD have a common origin [Toublanc et al, 1993;Kolon et al, 1998], which is supported by many reports of sibship among XX males and XX OT-DSD [Abbas et al, 1990;Ramos et al, 1996;Slaney et al, 1998;Maciel-Guerra et al, 2008].…”
Section: Discussionsupporting
confidence: 57%
“…The literature contains several reports of familial cases of true hermaphrodites [2,11,12,18,20,30], familial cases of XX males [1,9,21,23,24,26,35,39] and the two conditions co-existing in the same family [3, 15, 17, 19, 25, 27±29, 32, 33, 38]. Whenever molecular studies were done in families in the last category, most subjects were negative for the presence of Y chromosome material and most of them had genital ambiguity.…”
Section: Introductionmentioning
confidence: 99%
“…This condition reflects dysfunction at the level of sexual differentiation hormones, after testis or ovary formation (Smith and Sinclair, 1999). The histology of testicular tissue shows normal spermatogonia in the youngest patients and dysgenic tissue after 5 or 8 years of age (Toublanc et al, 1993). Ferguson-Smith (1966) hypothesized that the presence of testis and ovarian tissue in the gonads of 46,XX true hermaphrodites is caused by a mosaicism expression of TDF (SRY) related to X-chromosome inactivation.…”
Section: Copyright © 2001 S Karger Ag Baselmentioning
confidence: 99%